TEVAR for acute type B aortic dissection in pregnant women (35 weeks gestation) with Takayasu's arteritis after cesarean section: a rare case report and literature review - Taiyu Bi; Xiaotian Duan; Yipeng Yin (Frontiers in Cardiovascular Medicine)
BackgroundTakayasu's arteritis (TA) is an autoimmune disease that invades large arteries and mostly occurs in women of childbearing age. It leads to thickening and loss of elasticity of the arterial wall, and eventually vascular occlusion, aneurysm or dissection formation. Type B aortic dissection (TBAD) during pregnancy is a rare disease, which is mostly caused by the increase of blood volume in circulation during pregnancy, the effect of estrogen and progesterone on the aorta, or congenital diseases. TBAD in TA pregnant women is very rare, and the condition is often complicated. It is necessary to make a multidisciplinary treatment plan and determine the timing and method of operation to save the life of mother and fetus.Case descriptionWe report a pregnant woman at 35 weeks of gestation who presented to the emergency department with sudden and continuously unrelieved chest pain. She had TA for five years. Thoracoabdominal aortic computed tomography with angiography (CTA) showed acute TBAD. Her blood pressure was 209/73 mmHg and could not be lowered with Urapidil, therefore she was diagnosed with complex Stanford type B aortic dissection. She underwent cesarean section under general anesthesia, and the tracheal tube was not removed after surgery. Thoracic endovascular aortic repair (TEVAR) was administered under anesthesia 8 h after cesarean section. Intraoperative aortography showed that the stent blocked the tear of the intima of the aorta, and the false cavity was reduced. Her blood pressure was reduced to the normal range (140/90 mmHg or less), and the baby's vital signs were stable. They were discharged five days later. Use steroids to control TA throughout treatment. One year after the operation, the mother was healthy and the baby developed well.ConclusionEarly identification and accurate diagnosis should be made for acute TBAD in late pregnancy. Under the premise of stable hemodynamics, the fetus is delivered by cesarean section first and then TEVAR is the preferred treatment. The diagnosis and treatment plan of AD during pregnancy should be developed and implemented by multiple disciplines according to the vital signs of mother and fetus. TA pregnant women should take steroids during pregnancy, closely detect inflammatory indicators, and avoid pathogenic microbial infection, inflammatory state and complications. At the same time, the necessary follow-up is also the key to ensure the treatment effect.